Desenvolvimento de bebida láctea adicionada de ácido linoléico conjugado e ensaio clínico em mulheres obesas - Daniella Cristine Fialho Lopes (2010)
DEVELOPMENT OF A MILK DRINK ADDED OF CONJUGATED LINOLEIC ACID AND CLINICAL TRIAL IN OBESE WOMEN. The objective of this study research consisted in developing a chocolate flavored milk drink added of conjugated linoleic acid - CLA (BECLA) and to evaluate its effect in the dietary supplementation of obese women. The present work was approved by the Ethical Committee for Human Research of the Federal University of Minas Gerais - UFMG (Protocol No. 400/05, enclosed) and it was partially funded by the Research Foundation of Minas Gerais - FAPEMIG (Edital Universal 2006 466/06). Initially, aiming to choose a food that would be developed in this work, a survey was carried out on the estimates of CLA consumption in Brazil using food sources such as cow milk and its by-products (cheese, yoghurt, milk cream, condensed milk and butter), as well a beef. Data records on the Survey of Family Budgets (2002-2003) of the Brazilian Institute of Geography and Statistics (IBGE) were used. Those records showed an estimated CLA consumption of 637.9 mg. g-1 of fat, considering the above mentioned food sources. Based on this survey, we to undertake a laboratory procedure to develop a chocolate flavored milk drink added of CLA. Experiments were conducted in search of a better way to incorporate CLA, in its oily form, to the milk beverage, in order to minimize phase separation of the emulsion. The type of equipment (domestic blender and ultraturrax) and the blending time (1, 3 and 5 min) were tested. The domestic blender with speed 1 (11,500 rpm) for 3 min was more efficient than ultraturrax (11,000 rpm) for 5 min giving rise to a more stable mixture, evaluated by visual inspection and optical microscopy. Moreover this method allowed to verify that the fat drop size varied from 2.28 m to 12.23 m. A sensorial analysis test was used to determine the amount of CLA to be added to the milk drink in order to avoid any interference on the acceptance of the product. Three sensorial tests were applied. First, the triangular test was employed to verify the existence of sensorial difference between samples added of CLA and Canola oil (BECAN). This last beverage was developed to be used in the placebo group of the clinical experiment. Afterwards, the affective test was applied to evaluate the acceptance of BECLA and BECAN. At last, this same test was used in two chocolate flavored milk drinks added of CLA, one with 1.25% (BECLA 1.25%) and other with 2.5% (BECLA 2.5%). In the triangular test, 60% of the population were able to distinguish the taste of CLA showing that its incorporation should 22 be done with caution. In the acceptance test, the milk drink added of canola oil was preferred to the one with CLA. BECLA 1.25% was preferred to BECLA 2.5%. Continuing the study and based on the data obtained in the laboratory procedure, the two beverages were scaled up. At that stage, a study was carried out involving the evaluation of the chemical characteristics by the determination of moisture, ashes, proteins, lipids and the calculation of the amount of carbohydrates and caloric value. The stability of both milk drinks was evaluated by the measurement of pH and the oxidative stability using the TBARS method, as well as their final acceptance. The results of the chemical composition and the sensorial analysis had been confronted with the ones of a commercial drink. The energy value and the protein amount were higher in BECAN, followed by BECLA and the commercial product. This latter showed the least amount of lipids in relation to other drinks, and BECLA was the one that showed the highest value of this nutrient. The carbohydrate content was similar in BECLA and in the commercial drink and smaller in BECAN. The drinks developed in this study had the same value of ashes and moisture and, in relation with these beverages, the commercial product showed the smallest content of the first nutrient and highest of the second. No significant difference was found between the pH and TBARS values for BECLA and BECAN which indicates that the addition of CLA or canola oil showed no influence on the product stability during the period of study. The acceptance of BECLA and BECAN was similar and better than that of the commercial drink. After the production and analysis of the milk drinks the clinical experiment was started. Before the supplementation, three methods were applied for the evaluation of corporal composition of the population selected for the experiment. Thus, body fat percentages (%GC) of obese women obtained by anthropometry, bioimpedance (BIA) and dual energy X-ray absorptiometry (DEXA) were compared. The evaluation of body fat by DEXA, skinfold thickness (DC) and BIA showed averages of 44.1%, 39.8% and 34.3%, respectively, and were statistically different, with DEXA presenting the highest sensitivity, followed by DC and BIA. The clinical trial was randomized, double blind, with controlled placebo, and 28 volunteers ingested a daily amount of 400 mL of a milk drink added of 4 g of CLA (mixture of cis9, trans11CLA and trans10, cis12CLA) or placebo (canola oil) during 16 weeks. DEXA was used to evaluate the body composition at the beginning and the end of the experiment. Energy intake (EI) and the resting metabolic rate (RMR) were estimated at this same interval. The biochemical parameters that were evaluated consisted of fasting glicose, total cholesterol and its fractions, triglicerides, transaminases and reactive C protein which were measured in the months 0, 1, 2, 3 and 4. No significant change in the body composition, 23 EI and RMR was observed after the dietary supplementation of CLA added to the chocolate flavored milk drink. Furthermore, no significant modification was observed in the biochemical parameters, and no adverse effect was reported, indicating that the consumption of this fatty acid is not harmfull to health when consumed under the conditions described here.